PEMBINGKAIAN BERITA BOIKOT PRODUK ISRAEL DI MEDIA ONLINE REPUBLIKA.CO.ID - Radhitya, Maurizza; Toni , Ahmad (Media Mahardhika, 2024)
Republika is an online news portal founded by the Muslim community according to its readers. This news website is dominated by news which is dominated by news that contains Islamic elements. The aim of this research is to look for framing elements in 2 news articles written by the online media Republika.co.id. The research method used for analysis is Robert N. Entman's framing model, this analysis model has 4 elements, namely "Define Problems" (defining the problem), "Diagnose Cause" (estimating the cause of the problem), "Make Moral Judgment" (making a moral decision) , and “Suggest Remedies” (emphasizing resolution). The data collection technique used is a documentation collection technique, namely 2 news articles published on December 7 and December 19 2023. In the research results, the two news articles have a narrative telling readers to continue boycotting products affiliated with Israel. Republika Media has an Islamic view on the news it writes. This research is still new and there are still few researchers who have raised the issue or title of boycotts, moreover, the issue of boycotts is still hotly discussed by the public and there are still many media discussing news about the boycott of Israeli products. The researcher hopes that in the future many researchers will discuss the issue of boycotts, this research is still imperfect so that in the future it is hoped that it can be perfected by researchers who are interested in discussing the issue of boycotts using the framing analysis method initiated by any expert.